Comparative evaluation investigation of slag corrosion on Al2O3 and MgO-Al2O3 refractories via experiments and thermodynamic simulations. Issue 18 (15th December 2017) - Tang, H.Y.; Wu, G.H.; Wang, Y.; Li, J.S.; Lan, P.; Zhang, J.Q.
Abstract: Al2 O3 - and MgO-based refractories are widely used in the steel industry as lining materials for many metallurgical reactors. Due to their direct contact with slag and steel, they suffer corrosion and degradation, especially in the slag-line position, which limits their service performance. The purpose of this article is to obtain a better understanding of the corrosion behavior of the two refractories with different compositions of virtual steelmaking slags (wt%CaO/wt%SiO2 = 3.0–7.0, Al2 O3 : 18–35 wt%) using laboratory experiments and FactSage thermodynamic modeling. Pure Al2 O3 and MgO-Al2 O3 crucibles were adopted to simulate the two refractories, respectively, during the experiment. The results show that the degree of corrosion of both crucibles increases with an increase in slag basicity and a decrease in Al2 O3 content in the slag. The Al2 O3 crucible is more susceptible to corrosion than the MgO-Al2 O3 crucible, which is attributed to the effect of the slag penetrating through the Al2 O3 crucible matrix and substituting part of its matrix. For the MgO-Al2 O3 crucible, there was no obvious slag substitution, but a transition layer was found in the contact region between the crucible and the slag. The Al2 O3 in the crucible matrix reacts with slag to produce calcium alumina (CaAl12 O19, CaAl4 O7 ) and other complex oxides, while the MgO particles at the MgO-Al2 O3 crucible-slag interface were only surrounded by liquid slag without an obvious chemical reaction between them. The mechanism of corrosion was studied by experiments combined with thermodynamic calculations and with the establishment of a new corrosion model. This study is expected to provide a guide for the design of related refractories and slags in industrial applications.